2012
DOI: 10.1121/1.4708575
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mesoscale eddies and frontal zones on sound propagation at the Northwest Pacific Ocean

Abstract: The results of sound propagation through the warm mesoscale eddy in the region of Kuroshio at the Northwest Pacific are presented. The eddy core lies at point about 39° N, 149° E. Horizontal size of eddy was about 350 km, vertical size was more than 600 m. Continuous acoustic signals at the frequencies 232 Hz and 696 Hz were emitted by the sources towed at the depth of 100 m. Signals were received using a drifting system fitted with hydrophones. The results of experimental researches of sound propagation along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They have explored the relationship between eddies and acoustic propagation through observations and experiments. Akulichev, Bugaeva (Akulichev et al, 2012) reported the results of an acoustic survey in the KE region of the NW Pacific Ocean. They found that a mesoscale eddy significantly affected the horizontal propagation of acoustic signals through a towed source at a depth of 100 m. Liu, Piao (Liu et al, 2021) detected and tracked a mesoscale eddy in the western North Pacific Ocean, studying the eddy strength, oceanographic, and acoustic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…They have explored the relationship between eddies and acoustic propagation through observations and experiments. Akulichev, Bugaeva (Akulichev et al, 2012) reported the results of an acoustic survey in the KE region of the NW Pacific Ocean. They found that a mesoscale eddy significantly affected the horizontal propagation of acoustic signals through a towed source at a depth of 100 m. Liu, Piao (Liu et al, 2021) detected and tracked a mesoscale eddy in the western North Pacific Ocean, studying the eddy strength, oceanographic, and acoustic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The 3D structures of eddies can be hardly determined, but are generally acquired by constructing ideal eddy structure models [1][2][3][4], the effects of eddies on sound propagation are analyzed together with sound propagation models. Also a few experiments have been conducted to investigate the effects of mesoscale eddies on sound propagation [5][6][7]. In all, the existing studies about the effects of mesoscale eddies on sound propagation are mainly based on construction of eddy structure models, but the accuracy of models should be further validated.…”
Section: Introductionmentioning
confidence: 99%